An Assessment Of Attitude And Intention Of The Kedayan People In Practicing The Local Culture Among Different Levels Of Educational Background - Ros Aiza Mohd Mokhtar; Che Zarrina Sa'ari (International Journal of Arts and Sciences, USA, 2024)
This study was aimed to identify the differences of attitude and intention among the Kedayans in practicing their local culture based on different levels of educational background. Self-administered questionnaires were distributed to 414 respondents of the Kedayan ethnic in Sipitang, Sabah. The findings of this study revealed high correlation between the attitude towards local culture and their intention to continue practicing their local culture. Moreover, there was a significant statistical difference between their attitude and the intention to practice their local culture as far as different levels of educational background are concerned. As the respondents were from the Kedayan ethnicity residing in Sipitang, Sabah, it is recommended that future research may expand to other places in Sabah, Sarawak, Labuan, as well as Brunei, where the Kedayan people live. Future research may also look into other influences in practicing local culture, and this study can be applied to other ethnicities as well. This study has contributed and has extended knowledge to the Muslim society in general, especially in upholding their local culture. The findings should provide information to the governmental agencies and religious bodies as they promote local culture, as well as monitor the attitude and the practice of the local culture itself to conform to the Islamic principles.